BS 8468-3.2. Respiratory protective devices for use against chemical, biological, radiological and nuclear (CBRN) agents. Part 3.2. Air-purifying devices incorporating a hood for escape. Specification (3rd December 2019) - British Standards Institution,
No abstract available